Risk and Benefit in Personalised Medicine: An End User View. Issue 1 (2nd January 2017) - Kent, Alastair
Abstract : Personalised, or stratified, medicine is creating opportunities for the development of targeted therapies for many hitherto unmet clinical needs. For patients and families this is a cause for optimism. But it is unlikely that these novel therapies will provide complete cures. Rather they will address some but not all symptoms of a condition. In such circumstances, early engagement with patients and families will ensure that developments are targeted at those aspects of a condition which really matter, not just those that are easy to count. This will make the development process more efficient, and improve the likelihood that patients will be able to access therapies if the development process is successful.